The Semiotics of French Gestures - Calbrid, Geneviève (Indiana University Press, 1990)
The Semiotics of French Gestures is an important contribution in the field of semiotics, described on the original 1990 front cover flap text as follows: "Everyone gestures while speaking, in a specific and generally unconscious manner. What are the functions of gestures? What relationship do they have to speech? How do gestures work to create meaning? In this valuable book, Genevieve Calbris undertakes to answer those questions. Based on the author's own extensive experimental research, The Semiotics of French Gestures presents a systematic description and a detailed semiotic analysis of French gestures. The book aims to establish a structural semantics of the set of expressive gestures and facial expressions that accompany or replace spoken language.